Passive Dynamic Ankle Foot Orthoses Use in Civilian Patients with Arthritic Conditions of the Foot and Ankle. Issue 1 (March 2023) - Feng, Jing; Weiss, Jason; Thompson, Austin; Meeker, James E.
Background: Nonsurgical interventions such as bracing with ankle foot orthoses (AFOs) aim to assist, restore, and redirect weightbearing forces to address difficulty with mobilization. We identified a custom carbon fiber passive dynamic ankle foot orthosis (PDAFO) that was designed to meet the needs of military combat veterans. We sought to evaluate the off-loading properties of one model of PDAFO (ExoSym) in a civilian population. Methods: Civilian patients 18 years or older were prescribed a PDAFO by a single surgeon. Pedobarographic data were obtained using the Tekscan F-Scan system. With the insole, participants were instructed to walk at a self-selected pace along a 20 m walkway under 3 conditions: (1) insole placed in between the brace and foot (over); (2) insole placed between the brace and insole of the shoe (under); (3) without the brace, the insole was placed in between the foot and insole of the shoe in both limbs (without). For assessment, forefoot and heel areas were evaluated with respect to maximal force, force*time integral (FTI), maximal contact area, maximal contact pressure, pressure*time integral (PTI), center of force (COF) excursion. Results: Six patients with arthritic foot and ankle conditions completed pedobarographic assessment for analysis. The brace reduced forefoot maximal force and contact pressures by 66% and 49%, respectively (538 ± 236 to 185 ± 130 N [ P  < .001], and 99 ± 38 to 50 ± 24 P  < .002). Additionally, participants were observed to load the forefoot portion of the brace with double the maximum contact pressures compared to the unbraced foot (204 ± 57 to 99 ± 38 kPa, P  < .001). Conclusion: The results of this study showed that the PDAFO unloaded substantial force and pressure experienced by the forefoot. Participants loaded the brace to a greater extent than when going unbraced. ADAFO can provide measurable pressure relief for patients with arthritic conditions. Level of Evidence: Level IV, case series.